Dairy-Beef Retention Options - Basham, William (My University, 2020)
The efficient implementation of sexed semen from Holstein bulls has created an opportunity for dairy producers to change how dairy heifer replacement programs are managed. This technological advance has shortened the genetic lag interval in dairy herds by changing the historical need to produce a replacement heifer from every cow in the milking herd. Now producers can create future replacements from a targeted younger population with higher genetic value and breed other less desirable animals terminally to beef sires. This terminal mating to beef breeds has created a more favorable feedlot placement from commercial dairies than the usual Holstein steer. As these technologies have emerged dairies will now need evaluate marketing options and determine the most profitable choice for their business. In evaluating multiple marketing channels, including selling day-old dairy-beef crosses; back-grounding dairy-beef crosses and selling as four-weights; or retaining ownership until harvest, this research indicates, at current market conditions, that marketing dairy-beef crosses from the calf grower at approximately 400 pounds is the most profitable decision. Marketing day-old dairy-beef cross calves transfers future risk to the buyer and immediately takes the market premium over Holstein bull calves, however at current market conditions, this option is not the most profitable decision. When marketing four-weight dairy-beef calves directly from the calf ranch was evaluated, it was found that this market is the most profitable choice. Local raising costs in addition to day-old dairy-beef calf costs were found to be lower than the current market value for crossbred animals at this weight creating increased profit opportunity. This market is easily monitored at online cattle auction sites such as Overland Stockyards, where video markets sell thousands of animals from across the U.S. creating a well-traded exchange for market observation. Certainly the most risk and capital intensive marketing channel evaluated is maintaining ownership through harvest. When modeled with current market conditions this option was not found to be profitable, being the highest risk option based on the length of ownership and currently experiencing negative margins, this marketing channel is currently not the most profitable. It should be stated that the feeding period of these animals from birth to harvest is approximately 15 months and this length of time could span both profit and loss situations as market conditions change. As markets change, the most profitable channel for these dairy-beef calves will change also. Observing markets and maintaining a current marketing model is imperative to the producer to be prepared to respond to profitable marketing conditions.
Keywords: Dairy; Beef Cattle; Marketing; Risk management; Economics; Agriculture